Video-assisted Instruction for Pronunciation Improvement: An Intervention Study with Indonesian EFL Students - Mukarrama, Asma; Kalsum; Fajriansyah, Syukron (IALLTEACH (Issues In Applied Linguistics & Language Teaching), 2025)
This study examined the effectiveness of video-based instruction in improving the English pronunciation skills of 32 second-year students at a public senior high school in South Sulawesi. Using a one-group pre-test–post-test design over one month, students participated in eight sessions incorporating video materials that modeled vowels, consonants, stress, intonation, and rhythm. Quantitative data from pre- and post-tests were analyzed using SPSS. Results showed a significant improvement in pronunciation scores—from an average of 48.50 (“poor”) to 65.75—with a paired-samples t-test (t = –10.213, p = 0.000) confirming the statistical significance. Students made notable gains in producing unfamiliar phonemes and recognizing word stress, though intonation and rhythm remained more challenging. These findings suggest that video-assisted learning can enhance pronunciation outcomes in EFL classrooms. Practically, this implies that teachers should integrate multimedia tools into instruction to increase student engagement, provide authentic models, and foster more effective and inclusive pronunciation learning environments.